A novel loss-of-function KCNB1 gene variant in a twin with global developmental delay and seizures - Manville, Rían W.; Illeck, Claire L.; Santos, Cesar; Sidlow, Richard; Abbott, Geoffrey W. (Frontiers in Cellular Neuroscience, 2024)
Human voltage-gated potassium (Kv) channels are expressed by a 40-member family of genes essential for normal electrical activity and with numerous associations and linkages to excitability disorders. Function-altering sequence variants in the KCNB1 gene, which encodes the neuronally expressed Kv2.1 channel, are associated with neurodevelopmental disorders including developmental delay with or without epileptic activity. Here, we describe a 40-month-old fraternal twin who presented with severe neurodevelopmental delay. Electroencephalogram recordings at 19 months of age revealed poor sleep architecture and the presence of multifocal epileptiform discharges. The individual's fraternal twin was neurotypical and there was no family history of neurodevelopmental delay or seizures. Whole genome sequencing at 33 months of age for the proband revealed a de novo variant in KCNB1 [c.1154C>T/p.Pro385Leu], encoding a proline to leucine substitution at residue 385, in the extracellular region immediately preceding Kv2.1 transmembrane segment 6 (S6). Cellular electrophysiological analysis of the effects of the gene variant in heterologously expressed Kv2.1 demonstrated that homozygous Kv2.1-P385L channels were completely nonfunctional. Channels generated by 50/50 expression of wild-type Kv2.1 and Kv2.1-P385L to mimic the heterozygous status of the proband revealed a partially dominant-negative, 81% reduction in current magnitude. The dramatic loss of function in Kv2.1 is the most likely cause of the severe developmental delay and seizure activity in the proband, further enriching our phenotypic understanding of KCNB1 developmental encephalopathies.